2017
DOI: 10.1007/s10140-017-1559-6
|View full text |Cite
|
Sign up to set email alerts
|

Does radiography still have a significant diagnostic role in evaluation of acute traumatic wrist injuries? A prospective comparative study

Abstract: Radiography still remains as the first screening tool in acute traumatic wrist injuries and MDCT is complementary to it and used as a problem-solving tool or for preoperative planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…For our review, we only included the CT scaphoid sequences. 25 In recent studies, the interests of investigators focused more on the cone beam CT. 23,24 In contrast, similar findings were found on the different MRI sequences. According to Larribe et al, MRI contrast-(gadolinium) enhanced images showed highest sensitivity (83%) and specificity (100%) as compared to unenhanced sequences with 67 and 67%, respectively, which were statistically significant.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…For our review, we only included the CT scaphoid sequences. 25 In recent studies, the interests of investigators focused more on the cone beam CT. 23,24 In contrast, similar findings were found on the different MRI sequences. According to Larribe et al, MRI contrast-(gadolinium) enhanced images showed highest sensitivity (83%) and specificity (100%) as compared to unenhanced sequences with 67 and 67%, respectively, which were statistically significant.…”
Section: Discussionsupporting
confidence: 77%
“…In comparison to previous systematic reviews, six additional studies were included. [23][24][25][26][27][28] Males were affected in 49.2% of cases and the mean age was 34.1 AE 5.7 years. The overall incidence of occult scaphoid fractures was 21.8% (standard deviation [SD] 9.81).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation